Additive measurement of market concentration - Ginevičius, Romualdas; Čirba, Stasys (Journal of Business Economics and Management, 2009)
The main effect of globalization of the world markets is the increase of market concentration. The analysis and control of these processes largely depend on precise determination of the level of market concentration. Additive measures, evaluating the whole concentration curve, assess market concentration most effectively. The analysis shows that all currently used measures, including the most widely used Herfindahl index, have some limitations and, therefore, cannot adequately describe the market state. This index is still widely used because it is easy to calculate. However, now, when calculation is computer‐aided, this argument has hardly any sense. A possibility to assess the state of the market much more accurately, searching for new, more precise measures, has sense now. The accuracy of some particular measures may be defined by the total difference between the relative value of market criterion bearers in the market and their value calculated by the formula of a particular concentration measure.First Publish Online: 09 Jun 2011